Может ли религия способствовать демократии? - Богданова, Е. (Социология: теория, методы, маркетинг, 2007)
The paper explores whether a religion can facilitate democratic development. It demonstrates that Tocquevillean hypothesis retains more credibility in the light ofcontemporary sociological research than some of the more recent theses offered since 1990s. Further analysis suggests that democratic regime cannot be consolidated in a society with the dominant materialistic worldview. The article concludes with the discussion of prospective research that could shed more light on the conditions and mechanisms through which the religion would be conducive to a democracy.